Film histories : an introduction and reader - Grainge, Paul, 1972-; Jancovich, Mark; Monteith, Sharon (Edinburgh University Press, 2007)
The book is arranged chronologically, and each chapter contains an introduction by the editors on the key developments within the period, followed by a classic piece of historical research about that period. Various types of film history are undertaken in the articles, so that students can become familiar with different types of film historical research. For example, topics include the history of audiences; exhibition; marketing; censorship; aesthetic history; political history; and historical reception studies. The book is therefore designed to provide students with a narrative history spine while simultaneously introducing them to different approaches to the study and research of film history. Concentrating on the plurality of the ́⁰historical turń⁰₉ in film studies, this book demonstrates that film history is, and should be, about more than simply key films, directors and movements.